SAECG - advances in Brugada stratification. (19th May 2022) - Brito, J; Silverio Antonio, P; Silva, P; Couto Pereira, S; Valente Silva, B; Cunha, N; Nunes-Ferreira, A; Lima Da Silva, G; Neves, I; Cortez-Dias, N; J Pinto, F; Sousa, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Brugada syndrome (BrS) is a relevant cause of sudden cardiac death (SCD) in young adults. Several risk factors have been identified, but clinical decision making remains extremely challenging, particularly in asymptomatic patients. Purpose: To explore the usefulness of the non-invasive assessment of late potentials (LPs) based signal-averaged ECG (SAECG) for risk stratification in BrS. Methods: Prospective single-center study of patients with BrS included from 2003 to 2021. LPs were evaluated by SA-ECG with determination of the total filtered QRS duration (fQRS), root mean square voltage of the 40ms terminal portion of the QRS (RMS40) and duration of the low amplitude electric potential component of the terminal portion of the QRS (LAS40) in conventional and modified right precordial leads. The primary endpoint was the occurrence of malignant arrhythmic events (MAEs), defined as a composite of SCD or appropriate shocks. Uni- and multivariate Cox regression survival analyses were used to identify significant prognostic predictors considering the clinical, genetic, and electrocardiographic characteristics as well as the tercile distribution of the SAECG parameters. A risk score was computed incorporating the significant LPs variables and its usefulness for prognostic stratification was explored using Kaplan Meier survival analysis. Results: Our cohort consisted of 117 patients (mean age: 47±13 years, 33% male), including 75 (65%) with type 1 spontaneous pattern and 92 (79%) asymptomatic individuals. Symptoms at presentation included syncope in 16 pts (14%) and polymorphic VT/cardiac arrest in 4 (3.4%). During a median follow-up of 4.1±0.3 years, 8 pts (6.8%) suffered MAEs: 3 (2.6%) with SCD and 5 (4.3%) with appropriate shocks. The risk of events differed in relation to the several SAECG parameters (Table 1), increasing linearly with the fQRS duration determined either in the conventional (HR 1.03, 95% CI 1.01-1.06, p=0.008) or modified leads (HR: 1.03, 95% CI 1.01- 1.05, p=0.003). The SAECG score incorporated as risk markers a fQRS ≥113ms and a RMS40 <13 μV. Patients with both risk markers presented a 7-fold increased risk (HR 7.17, 95% CI 1.29-40, p = 0.025), independently of the baseline symptomatic status and ECG pattern. Conclusion: This study shows that the non-invasive assessment of LPs based on SAECG is useful for prognostic stratification of BrS. It was possible to identify a subset of patients presenting a high risk of events who may deserve individualized preventive strategies.